DTKS Verification Collaboration as the Practice of Strategic Communication by Handil Bakti Village Government - Ainun Nimatu Rohmah; Aji Muhammad Leonardo; Imam Muslim; Maria Imaculata Nggando Kelli Djoka; Misnaniah Misnaniah; Onedha Hosana; Sellvia Dwi Kristanti; Wahyudi Wahyudi; Xavier Fakhrusy Syakirin (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
Community service activities carried out by students can be a form of collaboration to support Government programs, one of which is the verification and validation of the Integrated Social Welfare Data (DTKS). The main problem faced by the local government in managing DTKS is the lack of human resources and objectivity of officers, so the data obtained often does not match the criteria. The Handil Bakti Village initiated the collaboration for verification and validation of DTKS with students as one of the joint-student service programs in the local government. As a form of strategic communication, the local government takes steps starting from planning, situation analysis, target analysis, goal formulation, message framework preparation, message dissemination strategy, and measurement and evaluation. Students verify and validate DTKS by conducting interviews with recipients in 14 RTs. The results obtained are accurate and objective DTKS data following the criteria set by the government and students gain an understanding of DTKS data collection.